2016
DOI: 10.1021/acs.est.6b02988
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of Saccharides and Divalent Cations in Sea Spray Aerosol During Two Phytoplankton Blooms

Abstract: Sea spray aerosol (SSA) is a globally important source of particulate matter. A mesocosm study was performed to determine the relative enrichment of saccharides and inorganic ions in nascent fine (PM) and coarse (PM) SSA and the sea surface microlayer (SSML) relative to bulk seawater. Saccharides comprise a significant fraction of organic matter in fine and coarse SSA (11 and 27%, respectively). Relative to sodium, individual saccharides were enriched 14-1314-fold in fine SSA, 3-138-fold in coarse SSA, but onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
203
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(240 citation statements)
references
References 84 publications
(251 reference statements)
22
203
0
Order By: Relevance
“…Colocated measurements of oligo/polysaccharides showed that saccharides were enriched in SSAs during IMPACTS, representing roughly 11% and 27% of the fine (D a < 2.5 μm) and coarse (2.5 < D a < 10 μm) organic mass. 53 Furthermore, the C*OH transition was observed to be enhanced in fine particles during the second bloom; concurrently, a maximum of saccharides in SSAs relative to seawater were observed by Jayarathne et al 53 Spectral deconvolution was performed for standard compounds to demonstrate the ability of NEXAFS to identify biologically relevant molecules ( Figure S9). Sodium alginate, galactose, and N-acetylglucosamine are common saccharides that contain the alcohol functionality.…”
Section: Acs Earth and Space Chemistrymentioning
confidence: 95%
See 1 more Smart Citation
“…Colocated measurements of oligo/polysaccharides showed that saccharides were enriched in SSAs during IMPACTS, representing roughly 11% and 27% of the fine (D a < 2.5 μm) and coarse (2.5 < D a < 10 μm) organic mass. 53 Furthermore, the C*OH transition was observed to be enhanced in fine particles during the second bloom; concurrently, a maximum of saccharides in SSAs relative to seawater were observed by Jayarathne et al 53 Spectral deconvolution was performed for standard compounds to demonstrate the ability of NEXAFS to identify biologically relevant molecules ( Figure S9). Sodium alginate, galactose, and N-acetylglucosamine are common saccharides that contain the alcohol functionality.…”
Section: Acs Earth and Space Chemistrymentioning
confidence: 95%
“…The results here demonstrate that the spectral deconvolution provides a reasonable estimation of the relative trends for the saccharide and amide contributions that is consistent with other studies of SSA. 16,53 3.4. Organic Volume Fractions (OVFs).…”
Section: Acs Earth and Space Chemistrymentioning
confidence: 99%
“…Mean enrichment factors for major ions demonstrate significant enrichment in fine SSA for K þ (1.3), Mg 2þ (1.4), and Ca 2þ (1.7), likely because of their interactions with organic matter. [5] The significant enrichment of Ca 2þ was observed in submicrometre SSA particles when particles were generated both from seawater sources in the laboratory and from ambient aerosol samples. [17] Investigations into the role of ions in SSA indicate that cations such as Mg 2þ and Ca 2þ can enhance organic species at the interface, which has implications for the surface packing of organic molecules and subsequent interfacial reactivity.…”
Section: Introductionmentioning
confidence: 97%
“…[2][3][4] The ocean represents a major source of primary aerosols; an estimated 2À100 Â 10 15 g of SSA is emitted from the ocean each year. [5] SSA is a globally important source of particulate matter, although its effect on the atmosphere is largely undetermined. [6] The composition of aerosols in the marine boundary layer has been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors still conclude that it is important to monitor the fluoride levels in the environment, especially because the main amount of fluoride comes from natural resources. For example, biomass burning may represent a major source of fluoride, in a form of fine particles which can be transported far away from the emitter [Jayarathne et al 2016; Weinstein and Davison 2003]. Years of research in fluoride have documented that this element accumulates in plants mostly from air pollution and it is absorbed directly through leaves.…”
Section: Introductionmentioning
confidence: 99%